Promoting Ag Awareness through Commodity Fact Sheets - Kathryn A. Stofer; Jessica Sullivan; Joy N. Rumble; Libbie Johnson (EDIS)
Increasing public awareness of Florida agriculture is a vital step in motivating the public to support agriculture. A basic understanding of Florida’s agricultural products, their impacts on the economy and the environment, and their availability contributes to Extension’s mission to sustain and enhance quality of life. This 3-page publication outlines a series of fact sheets with infographics related to specific Florida agricultural commodities. These fact sheets are intended to be visually appealing while presenting an overview of the commodity and its role in Florida agriculture. Written by Kathryn A. Stofer, Jessica Sullivan, Joy Rumble, and Libbie Johnson, and published by the Department of Agricultural Education and Communication, June 2016.